Catalytic deoxygenation of stearic acid over palladium supported on acid modified mesoporous silica - Lestari, S.; Beltramini, J.; Max Lu, G.Q.
Catalytic deoxygenation of stearic acid were investigated over palladium supported on acid modified mesoporous silica SBA15 and MCM-41. Liquid product analysis performed by gas chromatography shows that palladium supported on acid modified SBA15 was active toward deoxygenation product of n-pentadecane with selectivity up to 67(percent)after 5h reaction. Moreover, deoxygenation of stearic acid was also observed during the reaction that confirmed by mass spectroscopy the formation of nheptadecane.
Keywords: DEOXYGENATION; ACID MODIFIED SBA15; BIODIESEL